URANIUM DETECTION ASSOCIATION IN PARAÍBA WITH THE INCIDENCE AND PREVALENCE OF CANCER: A DOCUMENTARY STUDY - Sales Barros de Aguiar, Michelle; da Fonseca Julio de Macedo, Nicole; Alves Bezerra, Rebeca; Ester Silva Damasceno, Jullyanne; Furtado de Carvalho Feitosa, Sophia; dos Santos Vilar, Júlia; de Cássia Macêdo Correia Diniz, Rita; Noêmia Carvalho da Silva, Dayara; de Medeiros Amorim, Marcela; Andrade Nóbrega, Fernanda (Health and Society, 2024)
The relationship between exposure to radioactive elements, such as uranium, and the increase in cancer incidence has been the subject of several scientific investigations. Previous studies indicate that prolonged exposure to ionizing radiation may be associated with an increased risk of development of malignant neoplasms. The objective of the present study was to analyze the association between cancer and mortality in Paraíba, especially in some municipalities, where there is uranium. The present work is an ecological study that analyzes the Uranium Association with Cancer. Systematic revisions constitute instruments of integrative analysis of available scientific information, allowing to obtain responses based on evidence to clinically relevant questions. The results show a very strong and positive correlation between these two variables, with a correlation coefficient of 0.989. This indicates that as the incidence of neoplasms in women increases, there is also an increase in mortality from external causes between women, and vice versa. Statistical significance (SIG.) For this correlation is 0.000, indicating that the correlation is highly significant, with a confidence level of 99%. The analysis of the association between cancer and mortality in Paraíba, with special focus in municipalities with the presence of Uranium has revealed significant insights on the possible impacts of uranium exposure on public health. The data obtained indicate a worrying correlation between the presence of uranium and the increase in the incidence of neoplasms and mortality, especially in mining areas and regions with high concentrations of natural radiation.